# How do you simplify -10^2?

Feb 16, 2017

$- {10}^{2} = - 100$
it's helpful for the rest of your math life to view expressions in parentheses

#### Explanation:

note that $- {10}^{2}$ and ${\left(- 10\right)}^{2}$ give different results
$- {10}^{2} = \left(- 1\right) \left(10\right) \left(10\right) = - 100$
${\left(- 10\right)}^{2} = \left(- 10\right) \left(- 10\right) = 100$

think of $- {10}^{2}$ as $\left(- 1\right) \left({10}^{2}\right)$
and $- {10}^{2}$ is the same as $- {\left(10\right)}^{2}$

it's helpful for the rest of your math life to view expressions in parentheses

$- {10}^{2} = - 100$

$- 100$

#### Explanation:

This question is all about the order of operations: BEMDAS, or

• B (brackets)
• E (exponents)
• M (multiplication)
• D (division)
• S (subtraction)

The term $- {10}^{2}$ has two operations:

• multiplication between $- 1$ and 10, and
• the exponent which takes 10 to the second power

The E, or exponent, comes first:

$- {10}^{2} = - 1 \times {10}^{2} = - 1 \times 100 = - 100$

If we our question as ${\left(- 10\right)}^{2}$, then we'd have the B, or term within the bracket go first, which would give us $- 10$, which is then squared to get 100:

${\left(- 10\right)}^{2} = {\left(- 1 \times 10\right)}^{2} = \left(- 10\right) \left(- 10\right) = 100$